Insights from a Pseudo-Polygyny Cohort unmasking high sperm concentration and low forward motility as potential risk factors for recurrent failure of sperm donation IVF (RFDI), a subset of unexplained male infertility (UMI)Research in context - Tiancheng Zhang; Fan Dong; Xu Zhang; Ping Ping; Jin Qiu; Zhen Lu; Huachun Zou; Qian Xiao; Jianhui Li; Gaoyue Zhang; Huijuan Shi; Xiangfeng Chen (EBioMedicine)
Summary: Background: Unexplained male infertility (UMI) accounts for 15%–30% of cases of male infertility, but it is poorly understood. We investigated potential risk factors for UMI leveraging data from a sperm bank with a “one male to multiple females” structure to reduce confounding arising from female factors. Methods: Data on sperm donation provided by the Shanghai Human Sperm Bank (SHSB) to 39 qualified reproduction centres across China, along with information on IVF (In Vitro Fertilization) donor insemination cycles (DICs) performed at these centres and their reported outcomes, were retrieved from the Shanghai Human Sperm Bank (SHSB) for the period from 2004 to 2018. The association between semen parameters, demographic factors, and Cumulative Live Birth Rate from Donor Insemination (cLBR -DI) was analysed using linear regression analysis. Recurrent Failure of Sperm Donation IVF (RFDI) was defined as ≤1 pregnancy despite ≥4 DICs (indicating a cLBR -DI of ≤25%). Progressive Motility Rate (PR) refers to the percentage of grade (a + b) sperm among all sperm ((a + b)/(a + b + c + d)%). Forward Motility Rate (FR) refers to the percentage of grade (a + b) sperm among (a + b + c) sperm ((a + b)/(a + b + c)%). Sperm concentration<100 × 106/mL and FR > 95% was termed as normal group. The group with sperm concentration>200 × 106/mL or FR < 90% was termed high-risk RFDI (HR-RFDI). Logistic regression was used to assess correlations of RFDI. Propensity score matching (PSM) was used to match the RFDI and non-RFDI populations. Miscarriage conditions were also analysed in this study. Findings: We included 4734 qualifying sperm donors and 17,307 IVF DICs, of which 2447 donors had more than 4 DICs per donor, forming a Pseudo-Polygyny Cohort. 8.05% of the 2447 donors with normal semen parameters and more than 4 DICs met RFDI criteria. RFDI donors exhibited higher sperm concentration (96.00 [75.00, 130.00] vs. 90.00 [72.00, 122.22], p = 0.057) and lower Forward Motility Rate (95.12 [89.02, 97.01] vs. 96.59 [93.33, 97.30], p < 0.001) compared to non-RFDI. Forward Motility Rate, rather than Progressive Motility Rate, correlated with cLBR -DI Compared to the normal group, HR-RFDI had an over three-fold higher risk of RFDI before (RR = 3.48, 95% CI [1.94, 6.25], p < 0.0001) and after (OR = 3.04, 95% CI [1.92, 4.81], p < 0.0001) PSM adjustment. Notably, RFDI donors had higher miscarriage rates (10.80 ± 14.20% vs. 3.90 ± 8.50%, p < 0.0001) compared to non-RFDI donors. High-risk RFDI donors also had higher miscarriage rates (5.40 ± 9.20% vs. 4.20 ± 9.40%, p = 0.011) compared to low-risk RFDI donors. Interpretation: The negative impact of high sperm concentration on pseudo-polygyny cohort in vitro fertilization (IVF) outcomes strongly supports the hypothesis of a potential “inverted U-shape” relationship between sperm concentration and fertility. The superior correlation of FR with sperm donation IVF outcomes compared to PR suggests that FR may be a more meaningful measure of sperm motility in this context. The identification of an RFDI population, characterized by recurrent IVF failure and high miscarriage rates despite normal semen parameters, provides substantial evidence that the prevalence and severity of unexplained male infertility (UMI) may be greater than currently recognized. Therefore, a more comprehensive evaluation of male fertility should be considered in couples experiencing these issues. Funding: National Key R&D Program of China (2023YFC2705503), Fujian Province's Third Batch of Flexible Introduction of High-Level Medical Talent Teams (TD202307) and the National Key Technologies R&D Program (2023YFC2306700).